Terrestrial gamma radiation dose rates and radiological mapping of Terengganu state, Malaysia - Garba, Nuraddeen Nasiru Asiru (Elsevier Ltd., 2015)
Measurement of terrestrial gamma radiation dose (TGRD) rates in Terengganu state, Malaysia was carried out from 145 different locations using NaI[Tl] micro roentgen survey meter. The measured TGRD rates ranged from 35 to 340 nGy h-1 with mean value of 150 nGy h-1. The annual effective dose to population was found to be 0.92 mSv y-1. The data obtained were used in constructing the gamma isodose map using ArcGis 9.3 which shows the distribution of TGRD rates across the state.